From Risk to Resilience: How strategic Government Partnerships can Enhance Access to Insurance-Linked Credit for Smallholders in Zambia - Mascarenhas, Martina; Timu, Anne G.; You, Liangzhi (CGIAR System Organization, 2024)
The document explores innovative approaches to address the financial challenges faced by smallholder farmers amid increasing climate risks. It highlights the Risk-Contingent Credit (RCC) model, a bundled solution combining agricultural credit with weather-indexed insurance. Developed by ClimBeR and IFPRI, RCC provides a safety net for farmers by mitigating repayment obligations during climate-trigged losses, encouraging credit access without upfront collateral. The paper underscores the importance of partnerships, to scale RCC's reach and ensure its sustainability. The RCC model empowers marginalized smallholders, particularly women, to invest in climate-resilient agricultural practices while addressing supply and demand-side challenges. This approach demonstrates the transformative potential of inclusive financial tools and collaborative governance in fostering resilience, improving agricultural productivity, and ensuring food security in vulnerable regions.